DYNAMIC RESPONSE CALCULATION OF ROD UNDER ECCENTRIC TENSION AND COMPRESSION LOADINGS - CHU JunLiang (Jixie qiangdu, 2016)
The bars under tension and compression loadings widely exist in the structural engineering applications,which are the important loaded elements. This is because of the existence of all kinds of installed errors,the bars under tension and compression loadings are sometimes under eccentric tension and compression,Therefore,the dynamic responses of applied loading should be studied in order to ensure safety designs. In this paper,the dynamic loading responses of the straight bar with a constant cross-section and under loading of end axial eccentric harmonic tension and compression loads were studied,the little deformation hypothesis and the principle of linear superposition were used to divide the problem into two sub-problems,one is the axial tension and compression loading problem; another is the bending problem. The variations of the axial deformation and planar deflection with different disturbance frequencies were given,which is the basis of further dynamic designs. The research ideas together with methods of separation of variables and Fourier integration transformation technology can be employed to investigate the dynamic loading responses of the bars which are subjected to any eccentric axial load and distribution along the axial load.